2023
DOI: 10.1002/ajhb.23902
|View full text |Cite
|
Sign up to set email alerts
|

Body size, form, composition, and a healthy lifestyle associates with health‐related quality of life among Portuguese children

Abstract: ObjectivesThis study aimed to describe the relationship between body size, form, and composition, and children's lifestyle on health‐related quality of life (HRQoL).MethodsThis cross‐sectional study comprised 1333 children (9.05 ± 0.75 years; 683 females) living in mainland Portugal. Objective anthropometric measures were collected. Parents answered a standardized questionnaire related with children's lifestyle (e.g., sport participation, screen‐ and sleep‐time) and family socioeconomic status (e.g., parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(66 reference statements)
1
0
0
Order By: Relevance
“…Moreover, the current study indicates that being obese/overweight has no significant association with the IQOL change , which is consistent with a prior nationwide study in China that utilized both the Child Health Utility-9D (CHU-9D-CHN) and the Pediatric Quality of Life Inventory™ (PedsQL™) scale to measure the HRQoL of children, which without significant disparities in HRQoL scores among varying weight status. 52 Nevertheless, using IQOL importance instrument, our findings were consistent with other international studies 17,[53][54][55] and indicated that obesity/overweight individuals were associated with worse QoL. Due to the measuring facets as individualized preferences, the interpretations of results by analyzing how the person values these facets are noteworthy.…”
Section: Practical Implicationssupporting
confidence: 88%
“…Moreover, the current study indicates that being obese/overweight has no significant association with the IQOL change , which is consistent with a prior nationwide study in China that utilized both the Child Health Utility-9D (CHU-9D-CHN) and the Pediatric Quality of Life Inventory™ (PedsQL™) scale to measure the HRQoL of children, which without significant disparities in HRQoL scores among varying weight status. 52 Nevertheless, using IQOL importance instrument, our findings were consistent with other international studies 17,[53][54][55] and indicated that obesity/overweight individuals were associated with worse QoL. Due to the measuring facets as individualized preferences, the interpretations of results by analyzing how the person values these facets are noteworthy.…”
Section: Practical Implicationssupporting
confidence: 88%